2006
DOI: 10.1088/0953-2048/19/3/019
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-barrier and nanoscale superconducting devices

Abstract: Since the pioneering studies of Josephson and Giaever, the development of electronic devices has been a key research area in superconductivity. In conventional metallic superconductors, highly reliable tunnel junction fabrication techniques have enabled the application of superconducting devices in astronomy and metrology and have allowed the development of large scale integrated circuits for fast digital processing. These sub-micron heterostructure fabrication processes have also made possible the study of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…SnSe as Gas Sensors, YBaCuO or BiSrCaCuO thin films with different stoichiometric ratio between elements 3,4,5 , typically bolometric apparatus and so on. A lot of papers address the potentiality to fabricate magnetic nanostructures useful for many electronics applications, like high capacity memory support, sensors and actuators, and new spintronic valves 6,7 . An unexplored field of sensor applications is the use in chemically reactive or hostile environment (combustion) for monitoring spatial position and lifting of mechanical parts.…”
Section: Introductionmentioning
confidence: 99%
“…SnSe as Gas Sensors, YBaCuO or BiSrCaCuO thin films with different stoichiometric ratio between elements 3,4,5 , typically bolometric apparatus and so on. A lot of papers address the potentiality to fabricate magnetic nanostructures useful for many electronics applications, like high capacity memory support, sensors and actuators, and new spintronic valves 6,7 . An unexplored field of sensor applications is the use in chemically reactive or hostile environment (combustion) for monitoring spatial position and lifting of mechanical parts.…”
Section: Introductionmentioning
confidence: 99%
“…Static and dynamic couplings of two closely spaced junctions can play an important role in mesoscopic systems of superconducting electronics [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . Two Josephson junctions connected in series are particularly linked to each other by the equality of the flowing currents.…”
Section: Introductionmentioning
confidence: 99%
“…However, the spreads in junction parameters are quite large and hence they are not suitable for the device consisting of many junctions [3]. To overcome these drawbacks, some methods for making the junction from a micro-bridge were proposed, such as locally ion-damaged junction [5], [6], nano-junction [7], [8], and the variable-thickness bridge (VTB) junction. The first experiment on VTB done by Gubankov et al demonstrated Josephson properties at the temperature close to [9].…”
Section: Introductionmentioning
confidence: 99%
“…Simulations based on the transport of ions in matter: (TRIM) software indicate that the penetration depth of ions into the YBCO film without a protective layer on top was around 30 nm. However, the average implantation depth is 10-20 nm inward from the surface of the film; 0.1% of ions are implanted as far as 40 nm inward from the surface of the structure [7], [8]. The effect of irradiation induced damage on the electrical transport properties were characterized by the resistance-temperature curve measure with the four-point method.…”
Section: Introductionmentioning
confidence: 99%